2019
DOI: 10.3390/medicina55050210
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nanoemulsifying Drug Delivery System (SNEDDS) for Improved Oral Bioavailability of Chlorpromazine: In Vitro and In Vivo Evaluation

Abstract: Background and Objectives: Lipid-based self-nanoemulsifying drug delivery systems (SNEDDS) have resurged the eminence of nanoemulsions by modest adjustments and offer many valuable opportunities in drug delivery. Chlorpromazine, an antipsychotic agent with poor aqueous solubility—with extensive first-pass metabolism—can be a suitable candidate for the development of SNEDDS. The current study was designed to develop triglyceride-based SNEDDS of chlorpromazine to achieve improved solubility, stability, and oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 21 publications
(38 reference statements)
1
58
0
6
Order By: Relevance
“…There are few studies that have reported DPPH scavenging activity of luteolin better (IC 50 ≈ 2 µg/ml) than ascorbic acid (IC 50 ≈ 6 µg/ml) and tocopherol (IC 50 ≈ 10 µg/ml) [94]. Similarly, in another report, the DPPH scavenging activity of luteolin was found better (IC 50 = 1.8 µM, that is equivalent to about 0.5 µg/ml) than vitamin E, α-tocopherol (IC 50 = 5.2 µM) [95]. Despite the slightly different IC 50 of luteolin-loaded SNEDD from that of pure luteolin, the differences between DPPH scavenging activities at all tested concentration levels were not statistically significant.…”
Section: Antioxidant Activity (Dpph Radical Scavenging Activity)mentioning
confidence: 76%
“…There are few studies that have reported DPPH scavenging activity of luteolin better (IC 50 ≈ 2 µg/ml) than ascorbic acid (IC 50 ≈ 6 µg/ml) and tocopherol (IC 50 ≈ 10 µg/ml) [94]. Similarly, in another report, the DPPH scavenging activity of luteolin was found better (IC 50 = 1.8 µM, that is equivalent to about 0.5 µg/ml) than vitamin E, α-tocopherol (IC 50 = 5.2 µM) [95]. Despite the slightly different IC 50 of luteolin-loaded SNEDD from that of pure luteolin, the differences between DPPH scavenging activities at all tested concentration levels were not statistically significant.…”
Section: Antioxidant Activity (Dpph Radical Scavenging Activity)mentioning
confidence: 76%
“…Oil-in-Water (O/W) nano emulsions will be spontaneously formed when SNEDDS is exposed to GI fluids. The physicochemical properties of drugs encapsulated in nano emulsions significantly change and overcome the multiple bio-barriers in GI tract leading to improved oral bioavailability [9][10][11][12] .…”
mentioning
confidence: 99%
“…As a lipid-based drug formulation, SNEDDS has advantages such as thermodynamic stability, shelf stability, and high drug entrapment [14]. Triglycerides were also part of the composition of SNEDDS because they could easily form chylomicrons and pass through the lymphatic system [31]. Upon oral administration, the SNEDDS undergoes a self-emulsifying process in gastrointestinal fluids and forms o/w micelle droplets with a size of <100 nm [32], which are easy to disperse and promote a component distribution.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…As a lipid-based drug formulation, SNEDDS has advantages such as thermodynamic stability, shelf stability, and high drug entrapment [14]. Triglycerides were also part of the composition of SNEDDS because they could easily form chylomicrons and pass through the lymphatic system [31].…”
Section: Pharmacokinetic Studymentioning
confidence: 99%